Biparental inbreeding depression, genetic relatedness and progeny vigor in a wind-pollinated treeline species in Argentina - Seltmann, Peggy (2009)
Spatially restricted gene flow and resulting spatial genetic structure are generally considered as being the primary controlling factors in the dynamics of biparental inbreeding depression in a wide range of plant species. However, wind-pollinated angiosperm trees have not been adequately studied in this respect. The present study analyses the relationships between parental genetic similarity, outcrossing distances and progeny vigour in Polylepis australis (Rosaceae), a wind-pollinated treeline species endemic to Argentina. We investigated whether spatial genetic structuring occurs in anthropogenically fragmented P. australis woodlands of the Córdoba Mountains. We also performed a controlled crossing experiment using pollen collected from different distances. Genetic variability (using RAPD-PCR) and vigour (survival and N metabolism capacity) of the resulting progeny were contrasted with progeny from unmanipulated flowers. We found a continuous decrease in parental genetic similarity with spatial distance among mates and an increase in genetic variability, survival and N metabolism capacity in the progeny produced from pollen at increasing distances. However, our further results suggest fragment connectivity in P. australis through effective long-distance pollen-mediated gene flow with no effective inbreeding depression problems observed under present day conditions.